PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI SISTEM PERNAPASAN TERHADAP KELAS IX-2 SMP NEGERI 7 MEDAN TAHUN AJARAN 2018/2019 - Siregar, Heppy Juriver (Jurnal Sabilarrasyad, 2019)
The purpose of this study was to determine whether there was an increase in learning outcomes of Respiratory System Material Biology through the Think Pair Share (TPS) Type Cooperative Learning Model (TPS) class IX-2 SMP Negeri 7 Medan in the 2018â€“2019 academic year. This research is a Classroom Action Research (PTK). Classroom action research, namely Clasroom Action Research. The place of this research is SMP Negeri 7 Medan class IX-2 Semester II of the 2018/2019 academic year. Of the 33 students in the second cycle, 94% were declared complete, while 2 students had not yet experienced completeness with an average value of 87.33. Thus, in the second cycle the writer concludes that the students' scores have reached the KKM score. This research is stopped and there is no need to continue to the next cycle. Based on the results of this study, it can be concluded that the Think Pair Share (TPS) Cooperative Learning Model has an effect on learning outcomes and there is an increase in the learning outcomes of students in class IX-2 SMP Negeri 7 Medan in the 2018/2019 Learning Year.Â Keywords: Think Pair Share (TPS) Type Learning Model, Learning Outcomes, Respiratory System.